Analysis of Inventory Accounting Information System at PT. Namasindo Plas Medan - Marudut Lumban Gaol; Rahima Purba; Soulthan Saladin Batubara (Budapest International Research and Critics University, 2022)
The application of an accounting information system on inventory will provide many benefits for the company and management in running their business. Inventory has an important role, namely as a physical economic resource that needs to be held and maintained to support the sales process. This study aims to determine the inventory accounting information system at PT Namasindo Plas Medan. The method used is descriptive qualitative. The results show that the administrative system has been changed from a manual system to a computerized system that produces output that is useful for each user of the information. This is evidenced by the fact that all the components needed to support a valid system are owned by PT Namasindo Plas Medan and there are elements of internal control.